SISTEM INFORMASI DESA SEBAGAI MEDIUM INTEGRASI DAN KOMUNIKASI STAKEHOLDER DAN MASYARAKAT DESA - FANNY HENDRO ARYO PUTRO; TOPAN SETIAWAN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Information technology become increasingly important instruments, including their application in bureaucratic structures. The contemporary Indonesian village bureaucracy is a effectively efficient bureaucracy, leading to accountable governmental governance. The village information system is believed to contribute to that effort. This article will see how the village information System was developed and its contribution as a media communication, related to the development of village community. This article is a literature review, with a data source secondary is a publication, documents and other artifacts that give explanations to the theme of this study. The results of the village information System provide a positive contribution to the communication of stakeholders with the village community. The geographical condition of village villages in Indonesia does not all get Internet connection, so not all villages can be built SID infrastructure. In need of the distribution of communication infrastructure – information in Indonesia, To ensure facilities for the development of village information systems.